Valsalva maneuver using a Handmade Device in Supraventricular Tachycardia Reversion; a Quasi Experimental Study - Motamedi, Maryam; Akbarzadeh, Mohammad Ali; Safari, Saeed; Shahhoseini, Mehrnoosh (Archives of Academic Emergency Medicine, 2017)
Introduction: The use of vagal nerve stimulation is identified as a proper treatment option in patients with stable supraventricular tachycardia (SVT). This study aimed to assess the success of Valsalva maneuver via a handmade device in reversion of SVT. Methods: In this quasi experimental study, using a handmade device, vagus nerve stimulation was performed for SVT patients presenting to emergency department or cardiac intervention unit and the success rate and its related factors were assessed. Results: 100 patients with the mean age of 53.05 ± 13.70 years were studied (67% female). 12 (12%) cases were unable to do the maneuver. Out of the 88 (88.0%) patients who could perform the maneuver, 75 (85.2%) cases were unsuccessful. Dysrhythmia was controlled in 6 (6.8%) cases on the first attempt and in 7 (8.0%) cases on the second one (14.8% total success rate). 12 of the 13 cases (92.3%) with successful maneuver had history of SVT (p = 0.031). There was not any significant association between success rate and sex (p = 0.084), age (p = 0.744), or other medical histories (p ≥ 0.05). Conclusion: Based on the results of the present study, the success rate of Valsalva maneuver with the mentioned handmade device was calculated to be 14.8%. The only independent related factor of successful reversion was SVT history.